Time structure in men`s professional doubles tennis: does team experience allow finishing the points faster? - Martínez-Gallego, R.; Vives, F.; Guzmán, J. F.; Ramón-Llin, J.; Crespo, M. (International Journal of Performance Analysis in Sport, 2021)
This article provides information on the time structure of the doubles game in tennis and studies the influence of team experience on this time structure. The sample consisted of 2339 points corresponding to 19 complete ATP matches. Variables related to the point length and the number of shots per point were recorded, and teams were classified based on their experience playing together. The Mann-Whitney U test was performed to check the differences according to the types of teams and the Kruskal-Wallis test was used to check the differences depending on the match. The variables related to the duration and density of work presented lower values than in singles tennis. Regarding the data found based on the winning and losing team, the new teams used more time and more shots to win the points than the regular teams. Regarding the type of match, in the matches between two new teams, the duration of the points and the number of shots per point was greater compared to the other two types of matches. Offensive game strategies were adopted in the doubles matches, especially in regular teams, which reduced the length and density of the game.